Lung adenocarcinoma in a patient with Li–Fraumeni syndrome bearing a novel germ-line mutation, TP53R333Vfs*12. (24th June 2020) - Takahashi, Shodai; Shimazu, Kazuhiro; Kodama, Koya; Fukuda, Koji; Yoshida, Taichi; Taguchi, Daiki; Takahashi, Tsutomu; Nanjyo, Hiroshi; Shibata, Hiroyuki
Abstract: Germline mutations of TP53 are responsible for Li–Fraumeni syndrome in its 60–80%. We found a novel germline mutation, TP53: c.997del:p.R333Vfs * 12 (NM_000546.6, GRCh, 17:7670713..7670713). The proband is a 40-year-old female, who was suffered from osteosarcoma in her right forearm at her age of 11. She was also suffered from lung adenocarcinoma in her right upper lobe and bone metastasis in her right scapula at her age of 37. She was treated with gefitinib, an epidermal growth factor receptor-tyrosine kinase inhibitor (EGFR-TKI) because of EGFR mutation (L747-S752 del). Her bone metastasis became resistant after 1-year treatment. Bone metastasis had an additional EGFR mutation (T790M). The secondary treatment with osimertinib, an another EGFR-TKI, can successfully control the tumors for over 2 years. This TP53 mutation (R333Vfs * 12) was first found in lung adenocarcinomas. The therapeutic effect of osimertinib for this triple mutant lung adenocarcinoma is better than the previous report. Abstract : Lung adenocarcinoma arising in a Li–Fraumeni syndrome patient, bearing germline mutation, R333Vfs * 12 of TP53, is sensitive to epidermal growth factor receptor-tyrosine kinase inhibitors, such as gefitinib and osimertinib.